Implementasi Pembelajaran Deep Learning dalam Program Leadership Sebagai Strategi Pengembangan Karakter dan Kepemimpinan Siswa - Frendy Sasongko; Khoiriyah Khoiriyah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to examine and describe in depth the implementation of deep learning through a leadership program as a strategy for developing students’ character and leadership at SMP Islamic International School PSM Kediri. The research employed a qualitative approach with a case study design. The research subjects consisted of the principal, leadership program teachers, and students involved in the leadership activities. Data were collected through in-depth interviews, observations, and documentation, while data analysis followed the Miles, Huberman, and Saldaña model, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation of deep learning through the leadership program was systematically planned and integrated into school activities, positioning students as active participants in planning, implementing, and reflecting on leadership activities. The strategies applied included the integration of Islamic character values, reflective learning practices, and gradual assignment of leadership roles. The program had a positive impact on students’ character and leadership development, as reflected in increased responsibility, self-confidence, collaboration skills, and emotional maturity. However, several challenges were identified, including differences in students’ readiness, limited time allocation, and an evaluation system that has not yet been fully structured. Overall, deep learning through leadership programs shows strong potential as a holistic model for developing Islamic character and leadership among junior high school students. Keywords: Deep Learning, Leadership Program, Islamic Character, Student Leadership